Wall conditioning at the Wendelstein 7-X stellarator operating with a graphite divertor. (18th March 2020) - Goriaev, A; Wauters, T; Brakel, R; Brezinsek, S; Dinklage, A; Fellinger, J; Grote, H; Moseev, D; Sereda, S; Volzke, O
Abstract: Wall conditioning plays an important role in achieving record plasma performance on the superconducting stellarator Wendelstein 7-X (W7-X) by controlling plasma density and maintaining low levels of impurities. The development of the optimal wall conditioning strategy is of high importance for successful operation of the W7-X with a graphite divertor. The current strategy consists of initial wall conditioning applied prior to a physics experimental program and wall conditioning techniques executed during the plasma operation phase. The combination of baking and glow discharge cleaning provides a fast start to reliable plasma operation. Regular boronisation opens a new operational window of high plasma densities above 1 * 10 20 m −3 . Strong wall fueling remains, however, one of the main issues preventing plasma density control. A reliable solution is provided by application of He electron cyclotron resonance heating pulse trains, which are optimised to maximise fuel removal.